Ginsenoside Rb1 improves intestinal aging via regulating the expression of sirtuins in the intestinal epithelium and modulating the gut microbiota of mice - Zili Lei; Lei Chen; Qing Hu; Yanhong Yang; Fengxue Tong; Keying Li; Ting Lin; Ya Nie; Ya Nie; Hedong Rong; Hedong Rong; Siping Yu; et al. (Frontiers Media S.A., 2022)
Intestinal aging seriously affects the absorption of nutrients of the aged people. Ginsenoside Rb1 (GRb1) which has multiple functions on treating gastrointestinal disorders is one of the important ingredients from Ginseng, the famous herb in tradition Chinese medicine. However, it is still unclear if GRb1 could improve intestinal aging. To investigate the function and mechanism of GRb1 on improving intestinal aging, GRb1 was administrated to 104-week-old C57BL/6 mice for 6 weeks. The jejunum, colon and feces were collected for morphology, histology, gene expression and gut microbiota tests using H&E staining, X-gal staining, qPCR, Western blot, immunofluorescence staining, and 16S rDNA sequencing technologies. The numbers of cells reduced and the accumulation of senescent cells increased in the intestinal crypts of old mice, and administration of GRb1 could reverse them. The protein levels of CLDN 2, 3, 7, and 15 were all decreased in the jejunum of old mice, and administration of GRb1 could significantly increase them. The expression levels of Tert, Lgr5, mKi67, and c-Myc were all significantly reduced in the small intestines of old mice, and GRb1 significantly increased them at transcriptional or posttranscriptional levels. The protein levels of SIRT1, SIRT3, and SIRT6 were all reduced in the jejunum of old mice, and GRb1 could increase the protein levels of them. The 16S rDNA sequencing results demonstrated the dysbiosis of the gut microbiota of old mice, and GRb1 changed the composition and functions of the gut microbiota in the old mice. In conclusion, GRb1 could improve the intestinal aging via regulating the expression of Sirtuins family and modulating the gut microbiota in the aged mice.